2020
DOI: 10.1016/s2213-8587(20)30102-9
|View full text |Cite
|
Sign up to set email alerts
|

The importance of language in engagement between health-care professionals and people living with obesity: a joint consensus statement

Abstract: Obesity is a chronic condition that requires long-term management and is associated with unprecedented stigma in different settings, including during interactions with the health care system. This stigma has a negative impact on the mental and physical health of people with obesity and can lead to avoidance of health care and disruption of the doctors-patient relationship. There is significant evidence that simply having a conversation about obesity can lead to weight loss which translates into health benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 88 publications
1
78
0
12
Order By: Relevance
“…This will require concrete action from policy-makers, improve obesity education in undergraduate curriculums and educate healthcare professionals about obesity and how to avoid stigma. In an attempt to address the latest point, a consensus statement from multiple obesity experts and patients from the UK was issued [89].…”
mentioning
confidence: 99%
“…This will require concrete action from policy-makers, improve obesity education in undergraduate curriculums and educate healthcare professionals about obesity and how to avoid stigma. In an attempt to address the latest point, a consensus statement from multiple obesity experts and patients from the UK was issued [89].…”
mentioning
confidence: 99%
“…That was observed in studies that found that physical therapists 88 , occupational therapists 89 , physicians, nurses, and other professionals of a university hospital 90 , maintained harmful attitudes and stereotyped beliefs about obesity. Acording to these studies, this professionals use to judging patients according to negative adjectives as often as the general population, and this could result in the non-involvement of people living with obesity with the health system 91 .…”
Section: Discussionmentioning
confidence: 99%
“…First, at the patient level, this study has shown that eligible adults are more likely to have poorer educational attainment and higher deprivation indicating a form of inverse care law. Second, stigma surrounding obesity treatment and willingness or ability to meet strict criteria for accessing weight management services, or indeed capacity within these services, in England may present a barrier to uptake [12,13]. Third, studies on primary care practitioners in the UK suggest there is limited awareness of the role of metabolic surgery and perhaps even a level of bias against the provision of this treatment to patients who are obese [14].…”
Section: Discussionmentioning
confidence: 99%